The Influence Of Single Parent Parenting Style On Social Emotional Development Women Student Of Al-Istiqamah Ngatabaru Modern Islamic Boarding School - Beti Wulandari; Sagaf S. Pettalongi; Hamlan Hamlan (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2020)
This study was conducted in al-istiqamah ngatabaru modern islamic boarding school with sample of 50 students. Data were gathered through observation and questionnaires. The data were analysed using descriptive analysis approach. The results showed that the parenting style applied by each parents of students in general can be said to be quite democratic, but none of the parents of students who apply pure democratic parenting. Under certain circumstances, parents are authoritarian and in another circumstances parents are permissive. Based on the significant value of the Coefficients table, the significance value of 0,000 <0,05, then based on the known value of , while the Ttable value at the error level 5% = 2.011, thus the statement can be written that, tcount> (18.254 <2.011 ), the degree of the influence of single parent parenting style on social emotional behavior women student of al-istiqamah ngatabaru modern islamic boarding school also can be known through the magnitude of coefficient of determination (R Square) is 0.871 or 87.1%. This means that 12.9% is influenced by other factors not included in this study. so it can be concluded that single parent parenting style (X) parenting variable influential to emotional social development variable (Y), the result is significant hypothesis that there is positive influence between parenting parent single parent to emotional social development santriwati pondok pesantren modern Al-istiqamah Ngatabaru.